2023
DOI: 10.3390/ijms242015422
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Dysfunction and Hypoxia as Potential Mediators of Pain in Fabry Disease: A Human-Murine Translational Approach

Katharina Klug,
Marlene Spitzel,
Clara Hans
et al.

Abstract: Fabry disease (FD) is caused by α-galactosidase A (AGAL) enzyme deficiency, leading to globotriaosylceramide accumulation (Gb3) in several cell types. Pain is one of the pathophysiologically incompletely understood symptoms in FD patients. Previous data suggest an involvement of hypoxia and mitochondriopathy in FD pain development at dorsal root ganglion (DRG) level. Using immunofluorescence and quantitative real-time polymerase chain reaction (qRT PCR), we investigated patient-derived endothelial cells (EC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…These findings further support the notion that the pathogenesis of globotriaosylceramide deposits in AFD is not yet fully understood [44]. Concerning the pathology of cerebral vessels in AFD, the involvement has been observed [45][46][47][48] of the subarachnoidal arteries of medium size with narrowing of the lumen due to intimal fibrosis mixed with smooth muscle cells (SMC), with membrane abnormalities and stiffening of internal elastic tunica due to the total or partial change of the medial SMC and subsequent fibrosis and adventitial fibrosis. AFD involves smooth muscle too, but it is not clear whether the first step in Fabry vasculopathy involves endothelial cells, with a subsequent prothrombotic state, or if it begins in the smooth muscle cells of the arterial media layer [45][46][47][48].…”
Section: Molecular Pathogenesis Of Central Nervous System Involvement...supporting
confidence: 83%
See 3 more Smart Citations
“…These findings further support the notion that the pathogenesis of globotriaosylceramide deposits in AFD is not yet fully understood [44]. Concerning the pathology of cerebral vessels in AFD, the involvement has been observed [45][46][47][48] of the subarachnoidal arteries of medium size with narrowing of the lumen due to intimal fibrosis mixed with smooth muscle cells (SMC), with membrane abnormalities and stiffening of internal elastic tunica due to the total or partial change of the medial SMC and subsequent fibrosis and adventitial fibrosis. AFD involves smooth muscle too, but it is not clear whether the first step in Fabry vasculopathy involves endothelial cells, with a subsequent prothrombotic state, or if it begins in the smooth muscle cells of the arterial media layer [45][46][47][48].…”
Section: Molecular Pathogenesis Of Central Nervous System Involvement...supporting
confidence: 83%
“…Concerning the pathology of cerebral vessels in AFD, the involvement has been observed [ 45 , 46 , 47 , 48 ] of the subarachnoidal arteries of medium size with narrowing of the lumen due to intimal fibrosis mixed with smooth muscle cells (SMC), with membrane abnormalities and stiffening of internal elastic tunica due to the total or partial change of the medial SMC and subsequent fibrosis and adventitial fibrosis. AFD involves smooth muscle too, but it is not clear whether the first step in Fabry vasculopathy involves endothelial cells, with a subsequent prothrombotic state, or if it begins in the smooth muscle cells of the arterial media layer [ 45 , 46 , 47 , 48 ]. It has been reported that lyso-Gb3 plays a crucial role in the pathogenesis of Fabry vasculopathy, and it has been proposed that smooth muscle cells, rather than endothelial cells, represent the main target of cell accumulation.…”
Section: Molecular Pathogenesis Of Central Nervous System Involvement...mentioning
confidence: 99%
See 2 more Smart Citations